Parent Responses to Their Child's Pain: Systematic Review and Meta-Analysis of Measures. (9th March 2020) - Harrison, Lauren E; Timmers, Inge; Heathcote, Lauren C; Fisher, Emma; Tanna, Vivek; Duarte Silva Bans, Tom; Simons, Laura E
Abstract: Objective: Parent responses can have a major impact on their child's pain. The purpose of this systematic review is to (a) identify and describe measures assessing pain-related cognitive, affective, and behavioral responses in parents of children with chronic pain and (b) meta-analyze reported correlations between parent constructs and child outcomes (i.e., pain intensity, functional disability, and school functioning). Prospero protocol registration ID: CRD42019125496. Methods: We conducted a systematic search of studies including a measure of parent/caregiver responses to their child's chronic pain. Study characteristics and correlations between parent measures and child outcomes were extracted. Data were summarized and meta-analyzed. Results: Seventy-nine met inclusion criteria using 18 different measures of cognitive/affective ( n  = 3), behavioral ( n  = 5), and multidimensional responses ( n  = 10). Measures were used a median of three times (range 1–48), predominantly completed by mothers (88%), and primarily in mixed pain samples. Psychometrics of measures were generally adequate. Meta-analyses were based on 42 papers across five measures. Results showed that each of the cognitive, affective, and behavioral parent constructs we examined was significantly associated with pain-related functional disability. A small number of measures assessing parent cognitions and affective functioning were associated with higher child pain intensity; however, the majority were not. Conclusion: Findings demonstrate that there is a wealth of measures available, with adequate reliability overall but a lack of psychometrics on temporal stability. Synthesizing data across studies revealed small effects between parent responses and child functioning, and even smaller and/or absent effects on child pain intensity.